The Diary of Nannie Haskins Williams : A Southern Woman's Story of Rebellion and Reconstruction, 1863-1890 - Williams, Nannie Haskins, 1846-1930 (Book collections on Project MUSE., 2014)
In 1863, while living in Clarksville, Tennessee, Martha Ann Haskins, known to friends and family as Nannie, began a diary. The Diary of Nannie Haskins Williams: A Southern Woman's Story of Rebellion and Reconstruction, 1863--1890 provides valuable insights into the conditions in occupied Middle Tennessee. A young, elite Confederate sympathizer, Nannie was on the cusp of adulthood with the expectation of becoming a mistress in a slaveholding society. The war ended this prospect, and her life was forever changed. Though this is the first time the diaries have been published in full, they are well known among Civil War scholars, and a voice-over from the wartime diary was used repeatedly in Ken Burns's famous PBS program The Civil War. Sixteen-year-old Nannie had to come to terms with Union occupation very early in the war. Amid school assignments, young friendship, social events, worries about her marital prospects, and tension with her mother, Nannie's entries also mixed information about battles, neighbors wounded in combat, U.S. Colored troops, and lawlessness in the surrounding countryside. Providing rare detail about daily life in an occupied city, Nannie's diary poignantly recounts how she and those around her continued to fight long after the war was over--not in battles, but to maintain their lives in a war-torn community. Though numerous women's Civil War diaries exist, Nannie's is unique in that she also recounts her postwar life and the unexpected financial struggles she and her family experienced in the post-Reconstruction South. Nannie's diary may record only one woman's experience, but she represents a generation of young women born into a society based on slavery but who faced mature adulthood in an entirely new world of decreasing farm values, increasing industrialization, and young women entering the workforce. Civil War scholars and students alike will learn much from this firsthand account of coming-of-age during the Civil War. Minoa D. Uffelman is an associate professor of history at Austin Peay State University. Ellen Kanervo is professor emerita of communications at Austin Peay State University. Phyllis Smith is retired from the U.S. Army and currently teaches high school science in Montgomery County, Tennessee. Eleanor Williams is the Montgomery County, Tennessee, historian.